Analisa Pipa Heat Exchanger (Cooling Tube) Bervariasi Pada Turbine Guide Bearing Pembangkit Listrik Tenaga Air Siguragura - Tambos Sianturi (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2021)
A heat exchanger is a medium used to produce heat transfer from one fluid to another. Heat Exchanger can be used to raise the temperature or as a heater (regenerator) or lower the temperature or as a coolant (recuperator) depending on the view of heat transfer that occurs. Heat exchangers have been widely used in industries such as the chemical industry, paper industry, power plants, and other industries. In the example, each machine unit uses a heat exchanger media (especially rotary type machines) to keep the bearing temperature in normal temperature even though the unit is operated continuously or continuously. This study will analyze the temperature drop that occurs when the length of the heat exchanger pipe is added to the turbine guide bearing of PLTA Siguragura. From the research results, the maximum temperature on the guide bearing cooling tube reaches 47.3 [° C], the overall heat transfer coefficient on the guide bearing cooling tube is 98.87 [W / m²ºC], ∆Tmin on the guide bearing cooling tube installed (with 2 layers) is 14.1 [° C] and ∆Tmin which can be achieved with a cross-sectional area of ​​5.73 [m²] is 6.63 [° C]